PTU-077 Increased Long-Term Cancer Risk in Autoimmune Hepatitis (AIH): Relation to Immunosuppressive Drug Treatment. (17th August 2016) - Hoeroldt, BS; Gleeson, D; Shephard, K; Farquarson, N; MacFarlane, E; Karajeh, M; Poole, J
Abstract : Introduction: Background: Increased rates of hepatocellular (HCC) and recently, of extra-hepatic cancer have been reported in Autoimmune Hepatitis (AIH). Increased cancer rates in inflammatory bowel disease and following organ transplant have been linked to immunosuppressive (IS) drug therapy; this association has not been assessed in AIH. Aim . Evaluation relationship of cancer risk to non-steroid IS therapy in AIH Methods: 241 patients (197 F, age at diagnosis (median (range) 56 (2.5–87 yr), presenting 1971–2007 with AIH (1999 International Group criteria) and followed for ≥6 months. Cancers (ICD-10 code starting with C) were captured by clinical record review and individually linked to data from the English National Cancer Registry. In cases of discrepancy, records were re-checked and a consensus decision made. Patients were censored at death, liver transplant, changed diagnosis to PBC, cessation of follow up, or on 1/1/2014. We excluded cancers diagnosed before or within 6 months of AIH diagnosis or >30 days after follow-up ceased. Standardised incidence ratios (SIR; first cancer only) were calculated, relative to age-gender adjusted UK population rates. For non-melanoma skin cancer (NMSC), we considered only the years 2000–13, as there was under-reporting of NMSC to the registry prior to this. We estimated (pre-cancer) duration and cumulative dose of azathioprine (received by 208 patients) and total duration of all (non-steroid only) IS drug therapy. Results: Follow up was 12 (0.5–43 yr): total 3134 patient-years. There was development of (a) HCC in 10 patients (all with cirrhosis): SIR (95% CI) 41 (20–75); (b) lympho-proliferative cancer in 6 patients: SIR 2.94 (1.08–6.4: (c) ≥1 NMSC in 15 patients (2000–13): SIR 2.95 (1.65–4.87). SIR for all other extra-hepatic cancers remained above unity: 1.51 (1.07–2.07). Using a competing risks regression model, age-adjusted all-cancer risk was associated with duration (Hazard ratio (HR) 1.10 (1.01–1.20) and with cumulative dose (HR 1.07 (1.00–1.15) of azathioprine and with total duration of non-steroid IS therapy (HR 1.07 (1.01–1.14). Compared to those receiving non-steroid IS for <0.25 yr, age-adjusted all-cancer HR was 2.54 (1.13–5.72) and 8.71 (3.55–21.4) in those receiving IS for 0.25–10 yr and for >10 yr respectively. Conclusion: Patients with AIH have increased risk of hepatic and extra-hepatic cancer, including lymphoproliferative and NMSC. This risk is associated with duration of non-steroid IS drug therapy. Disclosure of Interest: None Declared